Effect of calcium chloride on emulsion stability of methyl-esterified citrus pectin. (1st December 2020) - Fan, Chuanhui; Chen, Xueling; He, Jianjun
Highlights: HMCP molecules are self-assembled into micelles in water. The morphology of HMCP micelles are irregular spheres, long rods, and arc-shaped. The molecules and the micelles of HMCP connect with each other at Ca 2+ . HMCP particles contain micelles and microgels. HMCP particles are adsorbed on the surface of emulsion droplets. Abstract: High methyl-esterified citrus pectin (HMCP) molecules could be self-assembled into micelles in water. The morphology of HMCP micelles in water was irregular spheres, long rods, and arc-shaped. Most of HMCP molecules cross-linked with HMCP micelles in the presence of calcium chloride and increased the range of size distribution of HMCP micelles. A little number of HMCP molecules cross-linked with each other to form 80 nn ~ 200 nm microgel particles. Calcium chloride could improve HMCP emulsification when its concentration was more than 70 mmol/L. HMCP micelles could be adsorbed on the surface of emulsion droplets. The emulsion prepared with HMCP and calcium chloride was similar to the Pickering emulsion.